2021
DOI: 10.3390/ijms222011224
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibition Regulates Lipid Homeostasis in a Mouse Model of Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is an incurable and fatal neurodegenerative disorder of the motor system. While the etiology is still incompletely understood, defects in metabolism act as a major contributor to the disease progression. Recently, histone deacetylase (HDAC) inhibition using ACY-738 has been shown to restore metabolic alterations in the spinal cord of a FUS mouse model of ALS, which was accompanied by a beneficial effect on the motor phenotype and survival. In this study, we investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 86 publications
6
42
0
Order By: Relevance
“…Interestingly, the authors reported a larger survival extension in males (76% in males, 24% in females) (Rossaert et al, 2019). The beneficial effect of the molecule was associated with a mitigation of lipid metabolism alterations and a restoration of global histone acetylation, but not with a reduction of astrocytosis nor microgliosis (Rossaert et al, 2019;Burg et al, 2021).…”
Section: Effect Of Hdac Inhibitors In Als Preclinical Models and Pati...mentioning
confidence: 97%
“…Interestingly, the authors reported a larger survival extension in males (76% in males, 24% in females) (Rossaert et al, 2019). The beneficial effect of the molecule was associated with a mitigation of lipid metabolism alterations and a restoration of global histone acetylation, but not with a reduction of astrocytosis nor microgliosis (Rossaert et al, 2019;Burg et al, 2021).…”
Section: Effect Of Hdac Inhibitors In Als Preclinical Models and Pati...mentioning
confidence: 97%
“…PC is a main source of acetylcholine in the CNS, and intake of PC can improve memory and learning and ameliorate cognitive decline in mouse models of dementia [118][119][120]. Elevated levels of PC have been reported in the CSF [65] and the spinal cord nuclear lipidome [70] of ALS patients, the spinal cords of FUS overexpression mice [68], the skeletal muscle of SOD1-G86R mice [67], and the motor cortex of SOD1-G93A mice [69]. Elevated levels of PC 44:8 and PC 36:4 have been found to be the most discriminatory in the CSF and plasma, being able to differentiate between slow-and fast-progression cases [61,65].…”
Section: Glycerophospholipids In Alsmentioning
confidence: 99%
“…metabolism [24], dysfunctions of T-regulatory (Tregs) lymphocytes [25], and defects in protein and RNA degradation and homeostasis [26] seem to act as major contributors to the progression of the disease. Most of the patients affected by ALS are characterized by an unknown etiology.…”
Section: Sphingolipids and Nervous Systemmentioning
confidence: 99%
“…Amyotrophic lateral sclerosis (ALS) is an incurable neurodegenerative disease characterized by the selective degeneration of motor neurons in the spinal cord, motor cortex, and brainstem [ 23 ]. The etiology of this pathology is still not well known; defects in the metabolism [ 24 ], dysfunctions of T-regulatory (Tregs) lymphocytes [ 25 ], and defects in protein and RNA degradation and homeostasis [ 26 ] seem to act as major contributors to the progression of the disease. Most of the patients affected by ALS are characterized by an unknown etiology.…”
Section: Introductionmentioning
confidence: 99%